A Faith Organization Scheme Model for Cloud - Vijaya Kumar, A; Hemanth Kumar, K; Tajudeen, J; Suresh, C (International Journal of Engineering and Technology, 2018)
IT Industries are rapidly migrating their businesses to the cloud architecture. The exponential change is because of elasticity and low-cost services offered by the cloud. The High-performance services offered at low price attract customers to run their businesses on cloud. Other side of the coin Faith on data privacy offered by the cloud is a key issue for every customer. Although the CSP ensure about the privacy and security of the userâ€™s data, but the customer reliability on cloud is still low. This paper briefed the necessity of faith organization scheme, it overviewed various recent works done in this area. The comparative analysis enables us the scope to focus on the lacking of Faith organization on cloud. This paper focuses on various existing techniques "provable data possession" and "evidences of hopelessness" which are used to control this problem to some extent. They will generate static report records and because of this poor reality strong mentor. In addition, threat models in some unspecified time in the future of these plans frequently accept a genuine owner and offer thoughtfulness regarding an untrustworthy cloud task. We proposed a Faith organization scheme to keep customer data safe. This work explains proposed model of faith organization and discuss various open issues in the relative area.Â